2008
DOI: 10.1542/peds.2008-0079
|View full text |Cite
|
Sign up to set email alerts
|

School Readiness

Abstract: School readiness includes the readiness of the individual child, the school's readiness for children, and the ability of the family and community to support optimal early child development. It is the responsibility of schools to be ready for all children at all levels of readiness. Children's readiness for kindergarten should become an outcome measure for community-based programs, rather than an exclusion criterion at the beginning of the formal educational experience. Our new knowledge of early brain and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(120 citation statements)
references
References 34 publications
1
105
0
7
Order By: Relevance
“…At the societal level, public investments in early childcare are increasing in many countries with the intention of reducing cognitive inequalities between disadvantaged and advantaged children (UNICEF Innocenti Research Centre, 2008). At the individual level, we suggest that health professionals recommend evidence-based interventions that could promote school readiness and academic achievement to at-risk families (High, 2008), because these professionals are in a privileged position to encourage the use of childcare among families, and particularly vulnerable ones (Silverstein, Grossman, Koepsell, & Rivara, 2003). In summary, this study suggests that the preferential use of formal childcare could prevent academic underachievement among disadvantaged children.…”
Section: Implications For Policy and Preventionmentioning
confidence: 79%
“…At the societal level, public investments in early childcare are increasing in many countries with the intention of reducing cognitive inequalities between disadvantaged and advantaged children (UNICEF Innocenti Research Centre, 2008). At the individual level, we suggest that health professionals recommend evidence-based interventions that could promote school readiness and academic achievement to at-risk families (High, 2008), because these professionals are in a privileged position to encourage the use of childcare among families, and particularly vulnerable ones (Silverstein, Grossman, Koepsell, & Rivara, 2003). In summary, this study suggests that the preferential use of formal childcare could prevent academic underachievement among disadvantaged children.…”
Section: Implications For Policy and Preventionmentioning
confidence: 79%
“…Early identification and attention to students' needs may significantly reduce delayed development (High, 2008); therefore, it is important that students are adequately prepared for kindergarten and that early identification and intervention of handwriting problems be provided.…”
Section: Handwriting Readinessmentioning
confidence: 99%
“…Establishing a standardized handwriting assessment to assess young writers is important because occupational therapists should be using valid tools in practice to indicate accurate ability and progress (Feder & Majnemer, 2003;Feder, Majnemer, & Synnes, 2000;Van Hartingsveldt et al, 2011) and to identify students with deficits as early as possible (Engel-Yeger, Nagauker-Yanuv, & Rosenblum, 2009;High, 2008). …”
Section: Assessing Handwriting Skillsmentioning
confidence: 99%
“…7 Identifying the breadth and severity of difficulties in school-readiness domains can maximize a child's schoolreadiness and increase the likelihood of academic success, which may improve future social, economic, and health outcomes. 8 Assessment and prediction of school readiness using the five skill areas mentioned above has been reported in the preterm infant population with evidence that neurodevelopmental assessment can both identify school readiness 5 and predict future school readiness from measures performed at 2 years of age. 9 A prospective, longitudinal study of preschool-age children with typical development demonstrated that language competence is a strong predictor of school readiness.…”
mentioning
confidence: 99%
“…12 Other aspects of educational performance, such as social interaction and communication, are often overlooked despite links between reduced educational attainment and poor long-term social and health-related outcomes. 7,8 When considering each school-readiness domain individually, the literature has demonstrated that in 5-year-old children with CP half present with one or more activity limitations in oromotor function and/or communication 13 and 16% are non-verbal. 13,14 Cohort studies of preschoolage children with CP have also addressed the domains of physical performance across the spectrum of severity in self-care 16 and social functioning.…”
mentioning
confidence: 99%